Analysis of Human Platelet Glycoprotein llb-llla by Fluorescein Isothiocyanate-Conjugated Disintegrins with Flow Cytometry - Liu, Chao-Zong; Wang, Yi-Wen R; Shen, Ming-Ching; Huang, Tur-Fu (Thrombosis and Haemostasis, 1994)
Disintegrins are a group of snake venom peptides which inhibit human platelet aggregation by acting as glycoprotein Ilb-IIIa (GPIIb-Ilia) antagonists. They are cysteine-rich, Arg-Gly-Asp (RGD)-containing peptides, and bind to GPIIb-Ilia complex on platelet membrane with a very high affinity (Kd, 10−7 ∼ 10−8 M). In this study, we analyzed GPIIb-Ilia complex on platelet membrane by flow cytometry using fluorescein isothiocyanate (FITC)-conjugated disintegrins as probes. Of these FITC-conjugated disintegrins, FITC-Rhodostomin is the most sensitive probe because Rhodostomin was conjugated with more FITC molecules than Trigramin and Halysin were. The binding fluorescence intensity of FITC-Trigramin (FITC-Tg), FITC-Halysin (FITC-Hy) and FITC-Rhodostomin (FITC-Rn) was measured in both resting and ADP-activated platelets of diluted human platelet-rich plasma. The binding fluorescence of FITC-disintegrins was abolished by EDTA and 7E3, a monoclonal antibody against GPIIb-Ilia. ADP markedly increased the fluorescence intensity of FITC-Tg and FITC-Hy bound on platelets especially when lower doses of these probes were used, whereas it had little effect on that of FITC-Rn. Therefore, FITC-Tg and FITC-Hy can be used for the detection of the activated platelets as noted by a higher ratio of fluorescence intensity (approx. 2-4) between ADP-activated and resting platelets as compared with that (approx. 1-1.3) in the case of FITC-Rn as the probe. The platelets from three patients with Glanzmann’s thrombasthenia were probed with FITC-disintegrins. As a result these three patients could be classified as type I thrombasthenia based on the extremely low level of GPIIb-Ilia detected by this method (<5% of normal value).